Preparation method of cobalt telluride-rich carbon nanocage for positive electrode carrier material of lithium-sulfur battery

By using carbon nanocage materials rich in cobalt telluride in the positive electrode support material of lithium sulfur batteries, the problem of insufficient electrocatalytic performance of existing materials is solved, efficient polysulfide conversion and structural stability are achieved, and suitable for large-scale electrochemical energy storage systems.

CN119852409AActive Publication Date: 2025-04-18UNIV OF SCI & TECH OF CHINA
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202510061771.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-15
Publication Date
2025-04-18
Estimated Expiration
2045-01-15

AI Technical Summary

Technical Problem

The existing lithium-sulfur battery positive electrode support materials have problems with low electron conductivity and durability of transition metal oxides and sulfides, which limits their electrocatalytic properties.

Method used

Using carbon nanocage materials rich in cobalt telluride, the nitrogen-doped grading pore structure of cobalt telluride nanoparticles is achieved by growing ZIF-67 on telluride nanowires and forming a nanocage structure through water etching and carbonization heat treatment.

Benefits of technology

It improves the electrocatalytic conversion capacity of polysulfides, enhances structural stability and cycle life, and is suitable for large-scale electrochemical energy storage systems.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119852409A_ABST
    Figure CN119852409A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a cobalt telluride-rich carbon nanocage for a positive electrode carrier material of a lithium-sulfur battery, which comprises the following steps: growing ZIF-67 on a Te nanowire, and carrying out simple water etching and one-step annealing treatment to obtain the cobalt telluride-rich carbon nanocage. The positive electrode material disclosed by the invention is simple in preparation process, excellent in cycling stability and high in specific capacity, and a novel design and preparation strategy is provided for a sulfur carrier material of a lithium-sulfur battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of positive electrode carrier materials for lithium-sulfur batteries, and in particular to a method for preparing a carbon nanocage rich in cobalt telluride for positive electrode carrier materials for lithium-sulfur batteries. Background Art

[0002] In order to cope with the energy crisis and environmental pollution, it is imperative to optimize the existing energy structure and seek renewable, clean and efficient new energy. As the mainstream form of electrochemical energy storage, secondary batteries are considered to be one of the most promising candidates due to their high efficiency and stability. Among them, lithium-ion batteries are the most widely used, which has a profound impact on people's production and life and has triggered a number of industrial changes. However, commercial lithium-ion batteries are close to the upper limit of theoretical energy density and have limited room for improvement. Lithium-sulfur batteries have high theoretical specific capacity and energy density, and their practical energy density is still 2 to 3 times that of today's commercial lithium-ion batteries. In addition, the active material sulfur in the positive electrode has abundant natural reserves and low cost, and compared with the heavy metal elements in lithium-ion batteries, sulfur has lower toxicity, which meets the needs of large-scale power storage.

[0003] At present, the strategy for the positive electrode carrier of lithium-sulfur batteries is to reduce the loss of electrochemically active substances and accelerate the conversion efficiency of intermediate products. Carbon materials have become one of the most common choices for carrier materials composited with sulfur due to their high conductivity, porous structural characteristics and low cost. At the same time, carbon materials are also excellent substrates for catalytic sites. Therefore, in recent years, various transition metal compounds have been composited with carbon materials to confine soluble polysulfides through physical adsorption and chemical anchoring, and at the same time, they are combined with catalytic sites to accelerate the reaction kinetics of electrochemically active substances. However, due to the limitations of low electronic conductivity and low durability of materials such as transition metal oxides and sulfides, their electrocatalytic performance for polysulfides is greatly limited. Transition metal tellurides have advantages such as high conductivity and high electrocatalytic activity, but due to their low natural abundance and high density, few people have applied them to electrode materials for lithium-sulfur batteries. Summary of the invention

[0004] In view of the above-mentioned problems currently existing in lithium-sulfur batteries, the present invention provides a method for preparing cobalt telluride-rich carbon nanocages for lithium-sulfur battery positive electrode carrier materials. The carrier material prepared by the method has a reasonable design, minimizes the content of transition metal tellurides, and achieves excellent electrocatalytic performance, so that polysulfides are efficiently converted during battery charging and discharging, has excellent structural stability and long cycle life, and is suitable for large-scale electrochemical energy storage systems.

[0005] In order to achieve the purpose, the present invention adopts the following technical scheme:

[0006] A method for preparing a carbon nanocage rich in cobalt telluride for a positive electrode carrier material of a lithium-sulfur battery is characterized in that: first, tellurium nanowires are prepared, then ZIF-67 is grown on the tellurium nanowires, then a nanocage structure is formed by water etching, and finally a carbonization heat treatment is performed to obtain a carbon nanocage rich in cobalt telluride. Specifically, the method comprises the following steps:

[0007] Step 1, dissolving 0.500-0.700 g of polyvinyl pyrrolidone in 19-23 mL of deionized water, adding 50.0-60.0 mg of sodium tellurite, 1-3 mL of 24-26 wt% ammonia water and 0.5-1.5 mL of 84-86 wt% hydrazine hydrate and stirring evenly, then transferring to a reactor for hydrothermal reaction to obtain a tellurium nanowire mother liquor; adding acetone to the tellurium nanowire mother liquor, centrifuging and separating, dispersing the obtained tellurium nanowires in 22-26 mL of anhydrous methanol to obtain a tellurium nanowire dispersion;

[0008] Step 2, dissolving 0.690-0.710 g of cobalt nitrate hexahydrate in 22-26 mL of anhydrous methanol to obtain a cobalt nitrate solution; dissolving 1.500-1.650 g of 2-methylimidazole in 22-26 mL of anhydrous methanol to obtain a 2-methylimidazole solution; adding the cobalt nitrate solution and the 2-methylimidazole solution to the tellurium nanowire dispersion obtained in step 1 and stirring at room temperature for reaction; washing the obtained product with anhydrous methanol and centrifuging to obtain ZIF-67 grown on the tellurium nanowires;

[0009] Step 3, dispersing the ZIF-67 grown on the tellurium nanowires obtained in step 2 in a mixed solution of water and anhydrous methanol, performing etching treatment by stirring, and centrifuging and freeze-drying the obtained product;

[0010] Step 4: subjecting the freeze-dried product obtained in step 3 to carbonization heat treatment in an argon atmosphere, and after naturally cooling to room temperature, a carbon nanocage rich in cobalt telluride for a positive electrode carrier material of a lithium-sulfur battery is obtained.

[0011] Preferably, in step 1, the temperature of the hydrothermal reaction is 160-200° C., and the reaction time is 2-4 hours.

[0012] Preferably, in step 2, the reaction time under room temperature stirring is 2 to 6 hours.

[0013] Preferably, in step 3, the volume ratio of water to anhydrous methanol is 0.25-2:1, and the amount of the mixed solution is 65-80 mL.

[0014] Preferably, in step 3, the etching treatment time is 0.5 to 2 hours.

[0015] Preferably, in step 4, the temperature of the carbonization heat treatment is 500-700°C, the heat treatment time is 1-3h, and the heating rate is 2-8°C min -1 .

[0016] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0017] The present invention uses ZIF-67 grown on tellurium wire as a precursor, and synthesizes nitrogen-doped hierarchical pore structure carbon nanocage materials loaded with cobalt telluride nanoparticles through water etching and one-step annealing treatment. The ZIF-67-derived carbon substrate exhibits structural characteristics of hierarchical pores, the mesopores increase the sulfur loading and mass transfer capacity during charging and discharging, and the micropores limit the shuttle effect of soluble polysulfides. The large number of cobalt telluride nanoparticles carried therein improve the chemical adsorption and catalytic conversion capabilities of polysulfides. The positive electrode material of the present invention has a simple preparation process, excellent cycle stability, and high specific capacity, and provides a new design and preparation strategy for sulfur carrier materials for lithium-sulfur batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 The present invention is a flow chart of the preparation method of the cobalt telluride-rich carbon nanocage.

[0019] Figure 2 This is a scanning electron microscope image of the e-CoTe@NC prepared in Example 1 of the present invention.

[0020] Figure 3 This is a transmission electron microscope image of the e-CoTe@NC prepared in Example 1 of the present invention.

[0021] Figure 4 It is a high-angle annular dark field scanning transmission image and element distribution map of the e-CoTe@NC prepared in Example 1 of the present invention.

[0022] Figure 5 It is a transmission electron microscope image of CoTe@NC prepared in comparative example 1 of the present invention.

[0023] Figure 6 3. It is the X-ray diffraction pattern of e-CoTe@NC prepared in Example 1 of the present invention and CoTe@NC prepared in Comparative Example 1.

[0024] Figure 7 It is a high-resolution X-ray photoelectron spectrum of Co 2p of e-CoTe@NC prepared in Example 1 of the present invention and CoTe@NC prepared in Comparative Example 1.

[0025] Figure 8 It is a high-resolution X-ray photoelectron spectrum of Te 3d of e-CoTe@NC prepared in Example 1 of the present invention and CoTe@NC prepared in Comparative Example 1.

[0026] Fig. 9 It is the N2 adsorption / desorption isotherm curve and pore size distribution curve of the e-CoTe@NC prepared in Example 1 of the present invention.

[0027] Fig.10 It is the N2 adsorption / desorption isotherm curve and pore size distribution curve of CoTe@NC prepared in Comparative Example 1 of the present invention.

[0028] Fig.11 The cyclic voltammetry curves of Li2S6 symmetric batteries assembled with e-CoTe@NC prepared in Example 1 of the present invention and CoTe@NC prepared in Comparative Example 1.

[0029] Fig.12 It is a graph showing the Li2S nucleation and deposition performance of a lithium-sulfur battery assembled from the e-CoTe@NC prepared in Example 1 of the present invention and the CoTe@NC prepared in Comparative Example 1.

[0030] Fig.13 It is a charge and discharge curve diagram of a lithium-sulfur battery assembled from the e-CoTe@NC prepared in Example 1 of the present invention and the CoTe@NC prepared in Comparative Example 1.

[0031] Fig.14 It is a cycle performance diagram of a lithium-sulfur battery assembled from the e-CoTe@NC prepared in Example 1 of the present invention and the CoTe@NC prepared in Comparative Example 1.

[0032] Fig.15 It is a rate performance diagram of a lithium-sulfur battery assembled from the e-CoTe@NC prepared in Example 1 of the present invention and the CoTe@NC prepared in Comparative Example 1.

[0033] Fig.16 It is an electrochemical impedance spectrum of a lithium-sulfur battery assembled from the e-CoTe@NC prepared in Example 1 of the present invention and the CoTe@NC prepared in Comparative Example 1. DETAILED DESCRIPTION

[0034] In order to further illustrate the present invention, the preparation method of a novel high-performance lithium-sulfur battery cobalt telluride-rich carbon nanocage structure positive electrode carrier material provided by the present invention is described in detail below in conjunction with the embodiments and illustrated in conjunction with the accompanying drawings, but it should not be understood as limiting the scope of protection of the present invention.

[0035] Example 1

[0036] In this embodiment, carbon nanocages rich in cobalt telluride are prepared according to the following steps:

[0037] Step 1, dissolve 0.6g of polyvinyl pyrrolidone in 21mL of deionized water, add 0.0553g of sodium tellurite, 2mL of ammonia water and 1mL of hydrazine hydrate and stir evenly, then transfer to a reactor for hydrothermal reaction at a hydrothermal temperature of 180°C for 3h to obtain a tellurium nanowire mother liquor; add acetone to the tellurium nanowire mother liquor, then centrifuge it, and disperse the tellurium nanowires with 24mL of anhydrous methanol to obtain a tellurium nanowire dispersion.

[0038] Step 2, dissolving 0.699 g of cobalt nitrate hexahydrate in 24 mL of anhydrous methanol to obtain a cobalt nitrate solution; dissolving 1.575 g of 2-methylimidazole in 24 mL of anhydrous methanol to obtain a 2-methylimidazole solution; adding the cobalt nitrate solution and the 2-methylimidazole solution to the tellurium nanowire dispersion obtained in step 1 and stirring at room temperature for 4 hours; washing the obtained product with anhydrous methanol and centrifuging to obtain ZIF-67 grown on the tellurium nanowires.

[0039] Step 3: Disperse the ZIF-67 grown on the tellurium nanowires obtained in step 2 in 72 mL of a 1:1 mixed solution of water and methanol, stir for 1 hour for etching, and centrifuge and freeze-dry the obtained product.

[0040] Step 4: Place the freeze-dried product obtained in step 3 in a tube furnace at 600°C in an argon atmosphere for 2 h at a heating rate of 5°C min -1 After cooling naturally to room temperature, a carbon nanocage rich in cobalt telluride, which is used as a cathode support material for lithium-sulfur batteries, is obtained, which is recorded as e-CoTe@NC.

[0041] Depend on Figure 1 It can be seen that carbon nanocages loaded with cobalt telluride nanoparticles are synthesized by using ZIF-67 grown on tellurium wire as a precursor through simple water etching and one-step annealing treatment.

[0042] Figure 2 This is a scanning electron microscope image of the e-CoTe@NC obtained in this example. It can be observed that the sample can still maintain the basic rhombic dodecahedron structure after etching and annealing, and there are certain pores on the surface.

[0043] Figure 3 This is a transmission electron microscope image of the e-CoTe@NC obtained in this example. In the image, the channels left after the tellurium lines disappear, as well as the channel structure formed by etching, can be seen. The darker contrast portion is the uniformly distributed cobalt telluride nanoparticles.

[0044] Figure 4The high-angle annular dark field scanning transmission image and element distribution map of the e-CoTe@NC obtained in this example. The left image shows the uniform distribution of cobalt telluride nanoparticles, and the right image clearly shows that the C, N, Co, and Te elements are evenly distributed on the carbon nanocage.

[0045] Comparative Example 1

[0046] This comparative example prepares a carbon nanomaterial without a nanocage structure according to the following steps:

[0047] Step 1, dissolve 0.6g of polyvinyl pyrrolidone in 21mL of deionized water, add 0.0553g of sodium tellurite, 2mL of ammonia water and 1mL of hydrazine hydrate and stir evenly, then transfer to a reactor for hydrothermal reaction at a hydrothermal temperature of 180°C for 3h to obtain a tellurium nanowire mother liquor; add acetone to the tellurium nanowire mother liquor, then centrifuge it, and disperse the tellurium nanowires with 24mL of anhydrous methanol to obtain a tellurium nanowire dispersion.

[0048] Step 2: Dissolve 0.699 g of cobalt nitrate hexahydrate in 24 mL of anhydrous methanol to obtain a cobalt nitrate solution; dissolve 1.575 g of 2-methylimidazole in 24 mL of anhydrous methanol to obtain a 2-methylimidazole solution; add the cobalt nitrate solution and the 2-methylimidazole solution to the tellurium nanowire dispersion obtained in step 1 and stir at room temperature for 4 hours; wash the obtained product with anhydrous methanol, centrifuge and freeze-dry.

[0049] Step 3: Place the freeze-dried product obtained in step 2 in a tube furnace at 600°C in an argon atmosphere for 2 h at a heating rate of 5°C min -1 After naturally cooling to room temperature, a carbon nanomaterial without a nanocage structure was obtained, which was recorded as CoTe@NC.

[0050] Figure 5 This is the transmission electron microscopy image of CoTe@NC obtained in this comparative example. The contrast is relatively uniform and no carbon nanocage structure exists.

[0051] Figure 6 2 are X-ray diffraction patterns of the samples obtained in Example 1 and Comparative Example 1. The diffraction peaks of the two samples correspond to the standard diffraction pattern of CoTe (PDF#34-0420), indicating the presence of cobalt telluride.

[0052] Figure 7 The Co 2p high-resolution X-ray photoelectron spectra of the samples obtained in Example 1 and Comparative Example 1 are fitted to obtain the 2p 1 / 2 and 2p 3 / 2 The positions and intensities of the characteristic peaks of the spin-orbit peak and the spin-orbit peak are basically consistent, indicating that the etching process only changes the geometric structure of the material and does not affect its chemical state.

[0053] Figure 8 The Te 3d high-resolution X-ray photoelectron spectra of the samples obtained in Example 1 and Comparative Example 1 are fitted to obtain the 3d 3 / 2 and 3D 5 / 2 The spin-orbit peak, the position and intensity of the characteristic peaks of the two are basically the same.

[0054] Fig. 9 The N2 adsorption / desorption isotherm and pore size distribution curve of the e-CoTe@NC obtained in Example 1 show a hierarchical pore structure rich in micropores and mesopores.

[0055] Fig.10 The N2 adsorption / desorption isotherm and pore size distribution curve of CoTe@NC obtained in Comparative Example 1 show the presence of microporous structure and fewer mesopores, indicating that the etching treatment produces more mesopores.

[0056] The e-CoTe@NC obtained in Example 1 was used as the working electrode and the counter electrode material, and 0.5 mol L -1 The Li2S6 was dissolved in DME / DOL solution as the electrolyte to assemble a symmetric battery. e-CoTe@NC was used as the positive electrode, lithium foil as the negative electrode, Celgard2400 PP membrane as the separator, and 0.5 mol L -1 Li2S8 and 1 mol L -1 LiTFSI was dissolved in a DME and DOL solution with a volume ratio of 1:1 as the cathode solution. 1 mol L -1 LiTFSI was dissolved in a DME and DOL solution with a volume ratio of 1:1 and 0.1 mol L -1 LiNO3 solution was used as the anolyte, the catholyte was added to the positive electrode, and the anolyte was added to the negative electrode. The lithium-sulfur battery was assembled to test the Li2S nucleation and deposition performance. The sulfur-loaded e-CoTe@NC was used as the positive electrode, the lithium foil was used as the negative electrode, the Celgard 2400 PP diaphragm was used as the diaphragm, and 1 mol L -1 LiTFSI was dissolved in a DME and DOL solution with a volume ratio of 1:1 and 0.1 mol L -1 The solution of LiNO3 is used as the electrolyte to assemble the lithium sulfur battery. The above batteries are all button batteries.

[0057] The CoTe@NC prepared in comparative example 1 was assembled into various types of batteries in the same manner as described above.

[0058] The cyclic voltammetry curves of the symmetrical battery were tested on a CHI 760E electrochemical workstation. Fig.11The cyclic voltammetry curves of the Li2S6 symmetric battery of the samples obtained in Example 1 and Comparative Example 1 show that e-CoTe@NC exhibits a more obvious peak shape and a larger redox response current, indicating that the electrochemical reaction kinetics are enhanced.

[0059] Fig.12 The Li2S nucleation deposition performance diagram of the lithium-sulfur battery of the samples obtained in Example 1 and Comparative Example 1 shows that e-CoTe@NC exhibits the highest nucleation contribution capacity and the shortest time to reach the peak current, indicating that the reaction kinetics of Li2S nucleation is improved.

[0060] Fig.13 The charge and discharge curves of the lithium-sulfur batteries of the samples obtained in Example 1 and Comparative Example 1 show that e-CoTe@NC exhibits a smaller polarization potential (△E) and a higher degree of discharge completion (Q2 / Q1) than CoTe@NC, indicating that the catalytic conversion ability during the discharge process is effectively improved.

[0061] Fig.14 The cycling performance of the samples obtained in Example 1 and Comparative Example 1 at 0.2C is shown in Figure 1. The e-CoTe@NC still maintains 1027 mAh g after 100 cycles. -1 However, the discharge capacity of CoTe@NC decayed significantly after 100 cycles, reaching only 870 mAh g -1 .

[0062] Fig.15 It is a rate performance diagram of the lithium-sulfur battery of the samples obtained in Example 1 and Comparative Example 1. The cycle performances of the e-CoTe@NC and CoTe@NC batteries at 0.1C, 0.2C, 0.5C, 1.0C and 2.0C were tested respectively. As the current density increases, the e-CoTe@NC exhibits a smaller capacity decay. When the current density gradually decreases to 0.1C, the specific capacity can be restored to a higher value. In contrast, the capacity decay of the CoTe@NC battery is more severe, and it exhibits an extremely low specific capacity at high currents.

[0063] Fig.16 3 are the electrochemical impedance spectra of the samples obtained in Example 1 and Comparative Example 1. Compared with CoTe@NC, e-CoTe@NC exhibits a smaller charge transfer resistance, thereby significantly improving the charge transfer at the electrode interface and the redox reaction kinetics.

[0064] The above are merely exemplary embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a carbon nanocage rich in cobalt telluride for a positive electrode carrier material of a lithium-sulfur battery, characterized in that: First, tellurium nanowires are prepared, then ZIF-67 is grown on the tellurium nanowires, and then a nanocage structure is formed by water etching. Finally, a carbonization heat treatment is performed to obtain a carbon nanocage rich in cobalt telluride.

2. The preparation method according to claim 1, characterized in that: The following steps are involved: Step 1, dissolving 0.500-0.700 g of polyvinyl pyrrolidone in 19-23 mL of deionized water, adding 50.0-60.0 mg of sodium tellurite, 1-3 mL of 24-26 wt% ammonia water and 0.5-1.5 mL of 84-86 wt% hydrazine hydrate and stirring evenly, then transferring to a reactor for hydrothermal reaction to obtain a tellurium nanowire mother liquor; adding acetone to the tellurium nanowire mother liquor, centrifuging and separating, dispersing the obtained tellurium nanowires in 22-26 mL of anhydrous methanol to obtain a tellurium nanowire dispersion; Step 2, dissolving 0.690-0.710 g of cobalt nitrate hexahydrate in 22-26 mL of anhydrous methanol to obtain a cobalt nitrate solution; dissolving 1.500-1.650 g of 2-methylimidazole in 22-26 mL of anhydrous methanol to obtain a 2-methylimidazole solution; adding the cobalt nitrate solution and the 2-methylimidazole solution to the tellurium nanowire dispersion obtained in step 1 and stirring at room temperature for reaction; washing the obtained product with anhydrous methanol and centrifuging to obtain ZIF-67 grown on the tellurium nanowires; Step 3, dispersing the ZIF-67 grown on the tellurium nanowires obtained in step 2 in a mixed solution of water and anhydrous methanol, performing etching treatment by stirring, and centrifuging and freeze-drying the obtained product; Step 4: subjecting the freeze-dried product obtained in step 3 to carbonization heat treatment in an argon atmosphere, and after naturally cooling to room temperature, a carbon nanocage rich in cobalt telluride for a positive electrode carrier material of a lithium-sulfur battery is obtained.

3. The preparation method according to claim 2, characterized in that: In step 1, the temperature of the hydrothermal reaction is 160-200° C., and the reaction time is 2-4 hours.

4. The preparation method according to claim 2, characterized in that: In step 2, the time of the reaction under stirring at room temperature is 2 to 6 hours.

5. The preparation method according to claim 2, characterized in that: In step 3, the volume ratio of water to anhydrous methanol is 0.25-2:1, and the amount of the mixed solution is 65-80 mL.

6. The preparation method according to claim 2, characterized in that: In step 3, the etching treatment time is 0.5 to 2 hours.

7. The preparation method according to claim 2, characterized in that: In step 4, the carbonization heat treatment temperature is 500-700°C, the heat treatment time is 1-3h, and the heating rate is 2-8°C min -1 .

8. A cobalt telluride-rich carbon nanocage prepared by the preparation method according to any one of claims 1 to 7.

9. The cobalt telluride-rich carbon nanocage according to claim 8, characterized in that: The cobalt telluride-rich carbon nano cage is a nitrogen-doped hierarchical pore structure carbon nano cage material on which cobalt telluride nano particles are loaded.

Citation Information

Patent Citations

  • A preparation method of a negative electrode material of a sodium ion battery

    CN108963237A

  • CoTe nanowire-graphene composite material and preparation method thereof

    CN109742378A

  • Preparation method of hollow nano cube for water-based sodium-ion battery negative electrode material

    CN114824207A

  • Metal organic framework derived cobalt ditelluride-reduced graphene oxide composite material as well as preparation method and application thereof

    CN116314710A

  • Preparation of cobalt-cobalt disulfide heterojunction embedded nitrogen-sulfur co-doped carbon nanocage positive electrode material and application of cobalt-cobalt disulfide heterojunction embedded nitrogen-sulfur co-doped carbon nanocage positive electrode material in lithium-sulfur battery

    CN116504951A